2022
DOI: 10.1029/2022ja030260
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of the Moon's Magnetotail Plasma Environment

Abstract: This study investigates the lunar plasma environment when embedded within Earth's magnetotail. We use data from 10 years of tail crossings by the Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) spacecraft in orbit around the Moon. We separate the plasma environments by magnetosheath‐like, magnetotail lobe‐like, and plasma sheet‐like conditions. Our findings highlight that the lobe‐like plasma is associated with low densities and a strong magnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 76 publications
2
5
0
Order By: Relevance
“…Therefore, our results confirm the idea of Liuzzo et al. (2022), that the middle magnetotail is a natural plasma laboratory for in situ CS investigations across a wide range of plasma characteristics. Moreover, observations of such partially force‐free CSs provide a unique opportunity for the verification of models describing equilibrium for CSs without a normal magnetic field component, B n = 0, (e.g., Allanson et al., 2015; Neukirch, Vasko, et al., 2020, and references therein) and with a finite B n ≠ 0 (e.g., An et al., 2023; Artemyev, 2011; Mingalev et al., 2012; Vasko et al., 2014).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, our results confirm the idea of Liuzzo et al. (2022), that the middle magnetotail is a natural plasma laboratory for in situ CS investigations across a wide range of plasma characteristics. Moreover, observations of such partially force‐free CSs provide a unique opportunity for the verification of models describing equilibrium for CSs without a normal magnetic field component, B n = 0, (e.g., Allanson et al., 2015; Neukirch, Vasko, et al., 2020, and references therein) and with a finite B n ≠ 0 (e.g., An et al., 2023; Artemyev, 2011; Mingalev et al., 2012; Vasko et al., 2014).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…We can use it to estimate the CS's spatial scale (thicknesses) and current density. ARTEMIS started operating in 2011 and its measurements now encompass 12 years of observations (see large statistics of plasma and magnetic field characteristics in Liuzzo et al., 2022; Runov et al., 2023). In this study, we use data collected between 2012 and 2022, covering 11 years in total (one full solar cycle).…”
Section: Introductionmentioning
confidence: 99%
“…Ion temperature components, which are set as Tfalse‖0=T0=300 ${T}_{{\Vert }_{0}}={T}_{{\perp }_{0}}=300$ eV initially, grow to 3×Tfalse‖01 ${\sim} 3\times {T}_{{\Vert }_{0}}\sim 1$ keV and 4×T01.2 $4\times {T}_{{\perp }_{0}}\sim 1.2$ keV close to the magnetopause ( x / L ∼ −3) within the simulation time. Therefore, a transition layer forms in between the magnetosheath and the magnetosphere, where the ion temperature is as great as typical magnetospheric ion temperature at the lunar distance (see statistics by Artemyev, Angelopoulos, Hietala, et al., 2017; Liuzzo et al., 2022).…”
Section: Simulation Of Long‐term Ion Dynamicsmentioning
confidence: 99%
“…Recently, Liuzzo et al. (2022) performed a large statistical study of magnetic field and plasma parameters observed by ARTEMIS in the nightside magnetosphere, selecting intervals of the probe's location within 20° in longitude of the local midnight meridian (i.e., the GSE X ‐axis). They distinguish “magnetosheath‐like,” “magnetotail lobe‐like,” and “plasma sheet‐like” plasma environments using criteria which include magnetic field direction and magnitude and plasma density.…”
Section: Introductionmentioning
confidence: 99%
“…No selection was made according to geomagnetic activity or local plasma flow conditions. The study by Liuzzo et al (2022) has revealed broad dynamic ranges of field and plasma parameters variations. Certain characteristics, including high density (up to 10 cm −3 ) in "magnetotail lobe-like" and "plasma sheet-like" environments, |B x | < 5 nT and |B z | ≈ 10 nT in the "lobe-like" environment, and the prevalence of earthward fast flows in the "plasma sheet-like" environment, require further investigation.…”
mentioning
confidence: 99%